Study on Solutions for Early Dismantling of Aluminum Formwork Systems in High-Rise Building Construction - Pham, Phu-Anh-Huy; Pham, Quang-Nhat (Salehan Institute of Higher Education, 2024)
This paper evaluated the impact of early aluminum formwork (AF) removal on the structural integrity of reinforced concrete (RC) beam-slab systems, specifically focusing on punching shear capacity, deflection, and crack width. The study provided a comprehensive analysis of the AF system, detailing its erection and dismantling sequences while examining its advantages and disadvantages. Moreover, safety principles for early formwork removal were proposed in accordance with the Vietnamese code (TCVN 5574:2018). By utilizing calculation examples based on actual high-rise building constructions and employing the finite element method, the study offered practical guidelines for the safe and effective use of AF systems, balancing rapid construction with structural safety. The findings emphasized the importance of assessing punching shear, deflection, and crack width criteria at the time of formwork removal to ensure structural safety. Results indicated that RC beam-slab systems remain safe in terms of punching shear capacity, deflection, and crack width if the shoring span does not exceed 1.6m when the concrete reaches its design strength. Furthermore, early removal of AF was feasible when the concrete achieved a strength grade of B12.5, with a shoring span of up to 1.6 m and a minimum slab thickness of 200mm. This study also contributed novel insights into optimizing construction efficiency by offering practical guidelines for the safe and effective use of AF systems, thus providing valuable recommendations for construction professionals and engineers. Doi: 10.28991/CEJ-2024-010-10-07 Full Text: PDF